Does split-body resistance training routine performed two versus three days per week induce distinct strength and morphological adaptations in resistance-trained men? a randomized longitudinal study - Brigatto, F. A.; Benvenutti Bueno de Camargo, J.; Machado, Y. B.; Germano, M. D.; Aoki, M. S.; Volpi Braz, T.; Lopes, C. R. (International Journal of Strength and Conditioning, 2022)
The purpose of this study was to investigate the chronic effects of training muscle groups, through a split-body routine on 2 versus 3 days per week, on neuromuscular performance and morphological adaptations in resistance-trained men with the number of sets per muscle group equated between conditions. Twenty healthy men (28.8 ± 6.1 years [range 19 to 37 years]; 172.8 ± 5.1 cm; total body mass = 70.2 ± 7.4 kg; RT experience = 3.5 ± 0.8 years [range 2 to 5 years]; RT frequency = 4.4 ± 0.5 session·wk-1) volunteered to participate in this study. Subjects were randomly assigned into 2 experimental groups: (1) 2 sessions·wk-1 per muscle (G2x, n = 10), in which every muscle was trained twice a week with 9 sets or (2) 3 sessions·wk-1 per muscle (G3x, n = 10), in which every muscle was trained thrice a week with 6 sets. All other variables were held constant over the 8-week study period. No significant difference between conditions for maximal strength in the back squat and bench press, muscle thickness of the biceps brachii, triceps brachii, vastus lateralis and anterior quadriceps (rectus femoris and vastus intermedius) was detected. In conclusion, both G2x and G3x significantly enhance muscular adaptations, with a similar improvement noted between experimental conditions.